2000
DOI: 10.1007/pl00008155
|View full text |Cite
|
Sign up to set email alerts
|

Growth, ageing and death of a photoautotrophic plant cell culture

Abstract: Batch cultures of photoautotrophic cell suspensions of Chenopodium rubrum L., growing in an inorganic medium on CO2 under a daily balanced light-dark regime of 16: 8 h could be maintained for approximately 100 d without subcultivation. The long-lived cultures showed an initial cell division phase of 4 weeks, followed by a stationary phase of another 4 weeks, after which ageing and progressive cell death reduced the number of living cells and the cultures usually expired after another 3-4 weeks. These developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Thus the use of both phosphoric [17] and acetic acid [19] for acidification of plant extract prior to SPE was reported. Elution of retained IAA was accomplished by using either absolute [17,19] or 80% methanol [18]. The use of 80% methanol containing 1% of acetic acid was also described [15].…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 98%
See 3 more Smart Citations
“…Thus the use of both phosphoric [17] and acetic acid [19] for acidification of plant extract prior to SPE was reported. Elution of retained IAA was accomplished by using either absolute [17,19] or 80% methanol [18]. The use of 80% methanol containing 1% of acetic acid was also described [15].…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 98%
“…Typically, the plant extract of IAA in 80% methanol is acidified only after it has been transformed into an aqueous phase by vacuum evaporation [18,19,23]. To eliminate this time-consuming step and replace it by a simple dilution procedure, we studied the influence of various methanol concentrations on IAA retention on the C18 matrix.…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize the individual developmental stages of that cell culture, we investigated the respective patterns and metabolic interconversions of these phytohormones and their derivatives (Fußeder et al 1988b). Bearing in mind the "stay-green" mutants (e.g., Hauck et al 1997) and the green islets in pathogen-attacked leaves (Faiss et al 1997) we identified the point of no return from ageing in our cell cultures as that state at which addition of phytohormones could not reverse the process of ageing (Peters et al 2000). One of the genes whose expression is under the control of auxin turned out as the gene of a glycan-exohydrolase OrGEH that is essential for growth of the cell wall and therefore also for the growth of the cell culture (Dominguez et al 2014).…”
Section: Photoautotrophic and Other Cell Suspension Culturesmentioning
confidence: 99%